Frequency anomalies and characteristics of extratropical cyclones during extremely wet, dry, windy, and calm seasons in the extratropics - H. Binder; H. Wernli (Weather and Climate Dynamics)
Extreme meteorological seasons are highly relevant because of their severe impacts on many socioeconomic sectors. However, a global statistical characterisation of observed extreme seasons is challenging because at any specific location, very few such seasons occurred during the limited period with available reanalysis datasets. This study therefore uses 1050 years of present-day (1990–1999) climate simulations of the Community Earth System Model Large Ensemble (CESM-LE) and 71 years (1950–2020) of ERA5 reanalyses to systematically identify extremely wet, dry, windy, and calm seasons in the extratropics during winter and summer and to quantify the role of extratropical cyclones in their occurrence. Extreme seasons are defined as spatially coherent regions of extreme seasonal mean precipitation or near-surface wind. The results from the climate model and from ERA5 are mostly consistent, suggesting that the climate model captures the cyclone properties reasonably well. Compared to the climatology, extremely wet seasons are associated with positive anomalies in cyclone frequency in large parts of the extratropics. In the Southern Hemisphere (SH) storm track and at the downstream ends of the Northern Hemisphere (NH) storm tracks, cyclones contributing to wet winters are also anomalously intense and typically originate unusually far to the west and south, while in the subtropical North Atlantic and over the eastern Mediterranean, they are on average more stationary than in the climatology. Windy seasons are often associated with anomalously few but particularly intense cyclones, especially during winter. Positive anomalies in both cyclone frequency and intensity are found in the southern North Atlantic during winter, which suggests that windy winters in this region occur during southward shifts in the position of the main storm track. The patterns of dry and calm seasons mainly contrast with those of wet and windy seasons; i.e. they are often characterised by particularly few or weak cyclones or a combination thereof. In all four types of extreme seasons, there is remarkably large spatial and seasonal variability in the cyclone properties, especially over the continents. Overall, it can be concluded that (i) anomalies in the seasonal frequency and/or intensity distribution of extratropical cyclones are crucial for the occurrence of many extreme seasons in the extratropics and (ii) this link shows substantial geographical and seasonal variability.